Recent Advances and Perspectives of Lewis Acidic Etching Route: An Emerging Preparation Strategy for MXenes - Huang, Pengfei; Han, Wei‑Qiang (Nano-Micro Letters, 2023)
Since the discovery in 2011, MXenes have become the rising star in the field of two-dimensional materials. Benefiting from the metallic-level conductivity, large and adjustable gallery spacing, low ion diffusion barrier, rich surface chemistry, superior mechanical strength, MXenes exhibit great application prospects in energy storage and conversion, sensors, optoelectronics, electromagnetic interference shielding and biomedicine. Nevertheless, two issues seriously deteriorate the further development of MXenes. One is the high experimental risk of common preparation methods such as HF etching, and the other is the difficulty in obtaining MXenes with controllable surface groups. Recently, Lewis acidic etching, as a brand-new preparation strategy for MXenes, has attracted intensive attention due to its high safety and the ability to endow MXenes with uniform terminations. However, a comprehensive review of Lewis acidic etching method has not been reported yet. Herein, we first introduce the Lewis acidic etching from the following four aspects: etching mechanism, terminations regulation, in-situ formed metals and delamination of multi-layered MXenes. Further, the applications of MXenes and MXene-based hybrids obtained by Lewis acidic etching route in energy storage and conversion, sensors and microwave absorption are carefully summarized. Finally, some challenges and opportunities of Lewis acidic etching strategy are also presented. Highlights: 1 As an emerging preparation strategy for MXenes, Lewis acidic etching has attracted increasing attention in the past few years benefiting from a series of merits. 2 Lewis acidic etching method is mainly presented from etching mechanism, terminations regulation, in-situ formed metals and delamination of multi-layered MXenes. 3 The applications of MXenes and MXene-based composites obtained by Lewis acidic etching route in energy storage and conversion, sensors and microwave absorption are carefully summarized.